HUBUNGAN METODE KANGURU DENGAN KENAIKAN BERAT BADAN PADA BAYI BERAT BADAN LAHIR RENDAH DI RUMAH SAKIT UMUM SRIKANDI IBI JEMBER - Afifah, Rizqiatul; Zakiyyah, Muthmainnah; Lestari, Dwi Anggun (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
The importance of the kangaroo method is carried out with the intention of providing closeness between mother and baby, this contact can be fulfilled through breastfeeding activities so that it can reduce stress and baby blues experienced by mothers who have just given birth. The purpose of this study was to determine the relationship between the kangaroo method and weight gain in low birth weight babies at the Srikandi IBI General Hospital, Jember. This study used a quantitative design with a cross sectional approach. The results showed that the kangaroo method at the Srikandi IBI Jember General Hospital, most of the respondents used the kangaroo method, namely 46 (95.8%) respondents. There was an increase in baby weight in low birth weight babies at the Srikandi IBI Jember General Hospital of 16.46. Based on statistical tests using chi square, the results obtained were p-value = 0.000 (α> 0.05) indicating that there is a relationship between the Kangaroo Method and infant weight gain in low birth weight babies at Srikandi IBI General Hospital Jember. Actions that can be taken provide useful information for pregnant women about baby care, especially the Kangaroo Method.